2016 focused update: clinical recommendations for cardiopulmonary exercise testing data assessment in specific patient populations. (2nd May 2016) - Guazzi, Marco; Arena, Ross; Halle, Martin; Piepoli, Massimo F; Myers, Jonathan; Lavie, Carl J
Abstract: In the past several decades, cardiopulmonary exercise testing (CPX) has seen an exponential increase in its evidence base. The growing volume of evidence in support of CPX has precipitated the release of numerous scientific statements by societies and associations. In 2012, the European Association for Cardiovascular Prevention & Rehabilitation and the American Heart Association developed a joint document with the primary intent of redefining CPX analysis and reporting in a way that would streamline test interpretation and increase clinical application. Specifically, the 2012 joint scientific statement on CPX conceptualized an easy-to-use, clinically meaningful analysis based on evidence-vetted variables in color-coded algorithms; single-page algorithms were successfully developed for each proposed test indication. Because of an abundance of new CPX research in recent years and a reassessment of the current algorithms in light of the body of evidence, a focused update to the 2012 scientific statement is now warranted. The purposes of this update are to confirm algorithms included in the initial scientific statement not requiring revision, to propose revisions to algorithms included in the initial scientific statement, to propose new algorithms based on emerging scientific evidence, to further clarify the application of oxygen consumption at ventilatory threshold, to describe CPX variables with an emerging scientific evidence base, to describe the synergistic value of combining CPX with other assessments, to discuss personnel considerations for CPX laboratories, and to provide recommendations for future CPX research.